5.27.15 Problems 1401 to 1500

Table 5.1195: Second order, Linear, non-homogeneous and constant coefficients

#

ODE

Mathematica

Maple

16272

\[ {}y^{\prime \prime }-6 y^{\prime }+13 y = 25 \sin \left (2 t \right ) \]

16273

\[ {}y^{\prime \prime }-9 y = 54 t \sin \left (2 t \right ) \]

16274

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = -78 \cos \left (3 t \right ) \]

16275

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = -32 t^{2} \cos \left (2 t \right ) \]

16276

\[ {}y^{\prime \prime }-y^{\prime }-20 y = -2 \,{\mathrm e}^{t} \]

16277

\[ {}y^{\prime \prime }-4 y^{\prime }-5 y = -648 t^{2} {\mathrm e}^{5 t} \]

16278

\[ {}y^{\prime \prime }-7 y^{\prime }+12 y = -2 t^{3} {\mathrm e}^{4 t} \]

16279

\[ {}y^{\prime \prime }+4 y^{\prime } = 8 \,{\mathrm e}^{4 t}-4 \,{\mathrm e}^{-4 t} \]

16280

\[ {}y^{\prime \prime }-3 y^{\prime } = t^{2}-{\mathrm e}^{3 t} \]

16281

\[ {}y^{\prime \prime }+4 y^{\prime } = -24 t -6-4 t \,{\mathrm e}^{-4 t}+{\mathrm e}^{-4 t} \]

16282

\[ {}y^{\prime \prime }-3 y^{\prime } = t^{2}-{\mathrm e}^{3 t} \]

16283

\[ {}y^{\prime \prime } = t^{2}+{\mathrm e}^{t}+\sin \left (t \right ) \]

16284

\[ {}y^{\prime \prime }+3 y^{\prime } = 18 \]

16285

\[ {}y^{\prime \prime }-y = 4 \]

16286

\[ {}y^{\prime \prime }-4 y = 32 t \]

16287

\[ {}y^{\prime \prime }+2 y^{\prime }-3 y = -2 \]

16288

\[ {}y^{\prime \prime }+y^{\prime }-6 y = 3 t \]

16289

\[ {}y^{\prime \prime }+8 y^{\prime }+16 y = 4 \]

16290

\[ {}y^{\prime \prime }+7 y^{\prime }+10 y = t \,{\mathrm e}^{-t} \]

16291

\[ {}y^{\prime \prime }+6 y^{\prime }+25 y = -1 \]

16292

\[ {}y^{\prime \prime }-3 y^{\prime } = -{\mathrm e}^{3 t}-2 t \]

16293

\[ {}y^{\prime \prime }-y^{\prime } = -3 t -4 t^{2} {\mathrm e}^{2 t} \]

16294

\[ {}y^{\prime \prime }-2 y^{\prime } = 2 t^{2} \]

16295

\[ {}y^{\prime \prime }+4 y^{\prime } = -24 t -6-4 t \,{\mathrm e}^{-4 t}+{\mathrm e}^{-4 t} \]

16296

\[ {}y^{\prime \prime }-3 y^{\prime } = {\mathrm e}^{-3 t}-{\mathrm e}^{3 t} \]

16297

\[ {}y^{\prime \prime }+9 y = \left \{\begin {array}{cc} 2 t & 0\le t <\pi \\ 0 & \pi \le t \end {array}\right . \]

16298

\[ {}y^{\prime \prime }+9 \pi ^{2} y = \left \{\begin {array}{cc} 2 t & 0\le t <\pi \\ -2 \pi +2 t & \pi \le t <2 \pi \\ 0 & 2 \pi \le t \end {array}\right . \]

16299

\[ {}y^{\prime \prime }+4 y = \left \{\begin {array}{cc} 0 & 0\le t <\pi \\ 10 & \pi \le t <2 \pi \\ 0 & 2 \pi \le t \end {array}\right . \]

16305

\[ {}y^{\prime \prime }+y^{\prime }-2 y = f \left (t \right ) \]

16306

\[ {}x^{\prime \prime }+9 x = \sin \left (3 t \right ) \]

16307

\[ {}4 y^{\prime \prime }+4 y^{\prime }+37 y = \cos \left (3 t \right ) \]

16308

\[ {}y^{\prime \prime }+4 y = 1 \]

16309

\[ {}y^{\prime \prime }+16 y^{\prime } = t \]

16310

\[ {}y^{\prime \prime }-7 y^{\prime }+10 y = {\mathrm e}^{3 t} \]

16311

\[ {}y^{\prime \prime }+16 y = 2 \cos \left (4 t \right ) \]

16312

\[ {}y^{\prime \prime }+4 y^{\prime }+20 y = 2 t \,{\mathrm e}^{-2 t} \]

16313

\[ {}y^{\prime \prime }+\frac {y}{4} = \sec \left (\frac {t}{2}\right )+\csc \left (\frac {t}{2}\right ) \]

16314

\[ {}y^{\prime \prime }+16 y = \csc \left (4 t \right ) \]

16315

\[ {}y^{\prime \prime }+16 y = \cot \left (4 t \right ) \]

16316

\[ {}y^{\prime \prime }+2 y^{\prime }+50 y = {\mathrm e}^{-t} \csc \left (7 t \right ) \]

16317

\[ {}y^{\prime \prime }+6 y^{\prime }+25 y = {\mathrm e}^{-3 t} \left (\sec \left (4 t \right )+\csc \left (4 t \right )\right ) \]

16318

\[ {}y^{\prime \prime }-2 y^{\prime }+26 y = {\mathrm e}^{t} \left (\sec \left (5 t \right )+\csc \left (5 t \right )\right ) \]

16319

\[ {}y^{\prime \prime }+12 y^{\prime }+37 y = {\mathrm e}^{-6 t} \csc \left (t \right ) \]

16320

\[ {}y^{\prime \prime }-6 y^{\prime }+34 y = {\mathrm e}^{3 t} \tan \left (5 t \right ) \]

16321

\[ {}y^{\prime \prime }-10 y^{\prime }+34 y = {\mathrm e}^{5 t} \cot \left (3 t \right ) \]

16322

\[ {}y^{\prime \prime }-12 y^{\prime }+37 y = {\mathrm e}^{6 t} \sec \left (t \right ) \]

16323

\[ {}y^{\prime \prime }-8 y^{\prime }+17 y = {\mathrm e}^{4 t} \sec \left (t \right ) \]

16324

\[ {}y^{\prime \prime }-9 y = \frac {1}{1+{\mathrm e}^{3 t}} \]

16325

\[ {}y^{\prime \prime }-25 y = \frac {1}{1-{\mathrm e}^{5 t}} \]

16326

\[ {}y^{\prime \prime }-y = 2 \sinh \left (t \right ) \]

16327

\[ {}y^{\prime \prime }-2 y^{\prime }+y = \frac {{\mathrm e}^{t}}{t} \]

16328

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = \frac {{\mathrm e}^{2 t}}{t^{2}} \]

16329

\[ {}y^{\prime \prime }+8 y^{\prime }+16 y = \frac {{\mathrm e}^{-4 t}}{t^{4}} \]

16330

\[ {}y^{\prime \prime }+6 y^{\prime }+9 y = \frac {{\mathrm e}^{-3 t}}{t} \]

16331

\[ {}y^{\prime \prime }+6 y^{\prime }+9 y = {\mathrm e}^{-3 t} \ln \left (t \right ) \]

16332

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = \cos \left ({\mathrm e}^{t}\right ) \]

16333

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = {\mathrm e}^{-2 t} \sqrt {-t^{2}+1} \]

16334

\[ {}y^{\prime \prime }-2 y^{\prime }+y = {\mathrm e}^{t} \sqrt {-t^{2}+1} \]

16335

\[ {}y^{\prime \prime }-10 y^{\prime }+25 y = {\mathrm e}^{5 t} \ln \left (2 t \right ) \]

16336

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = {\mathrm e}^{2 t} \arctan \left (t \right ) \]

16337

\[ {}y^{\prime \prime }+8 y^{\prime }+16 y = \frac {{\mathrm e}^{-4 t}}{t^{2}+1} \]

16338

\[ {}y^{\prime \prime }+y = \sec \left (\frac {t}{2}\right )+\csc \left (\frac {t}{2}\right ) \]

16339

\[ {}y^{\prime \prime }+9 y = \tan \left (3 t \right )^{2} \]

16340

\[ {}y^{\prime \prime }+9 y = \sec \left (3 t \right ) \]

16341

\[ {}y^{\prime \prime }+9 y = \tan \left (3 t \right ) \]

16342

\[ {}y^{\prime \prime }+4 y = \tan \left (2 t \right ) \]

16343

\[ {}y^{\prime \prime }+16 y = \tan \left (2 t \right ) \]

16344

\[ {}y^{\prime \prime }+4 y = \tan \left (t \right ) \]

16345

\[ {}y^{\prime \prime }+9 y = \sec \left (3 t \right ) \tan \left (3 t \right ) \]

16346

\[ {}y^{\prime \prime }+4 y = \sec \left (2 t \right ) \tan \left (2 t \right ) \]

16347

\[ {}y^{\prime \prime }+9 y = \frac {\csc \left (3 t \right )}{2} \]

16348

\[ {}y^{\prime \prime }+4 y = \sec \left (2 t \right )^{2} \]

16349

\[ {}y^{\prime \prime }-16 y = 16 t \,{\mathrm e}^{-4 t} \]

16350

\[ {}y^{\prime \prime }+y = \tan \left (t \right )^{2} \]

16351

\[ {}y^{\prime \prime }+4 y = \sec \left (2 t \right )+\tan \left (2 t \right ) \]

16352

\[ {}y^{\prime \prime }+9 y = \csc \left (3 t \right ) \]

16353

\[ {}y^{\prime \prime }+4 y^{\prime }+3 y = 65 \cos \left (2 t \right ) \]

16357

\[ {}4 y^{\prime \prime }+4 y^{\prime }+y = {\mathrm e}^{-\frac {t}{2}} \]

16358

\[ {}y^{\prime \prime }+4 y = f \left (t \right ) \]

16575

\[ {}y^{\prime \prime }-2 y^{\prime }-8 y = -t \]

16576

\[ {}y^{\prime \prime }+5 y^{\prime } = 5 t^{2} \]

16577

\[ {}y^{\prime \prime }-4 y^{\prime } = -3 \sin \left (t \right ) \]

16578

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = 3 \sin \left (2 t \right ) \]

16579

\[ {}y^{\prime \prime }-9 y = \frac {1}{1+{\mathrm e}^{3 t}} \]

16580

\[ {}y^{\prime \prime }-2 y^{\prime } = \frac {1}{{\mathrm e}^{2 t}+1} \]

16581

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = -4 \,{\mathrm e}^{-2 t} \]

16582

\[ {}y^{\prime \prime }-6 y^{\prime }+13 y = 3 \,{\mathrm e}^{-2 t} \]

16583

\[ {}y^{\prime \prime }+9 y^{\prime }+20 y = -2 t \,{\mathrm e}^{t} \]

16584

\[ {}y^{\prime \prime }+7 y^{\prime }+12 y = 3 t^{2} {\mathrm e}^{-4 t} \]

16593

\[ {}y^{\prime \prime }-4 y = t \]

16594

\[ {}y^{\prime \prime }+3 y^{\prime }-4 y = {\mathrm e}^{t} \]

16595

\[ {}y^{\prime \prime }+9 y = \sin \left (3 t \right ) \]

16596

\[ {}y^{\prime \prime }+y = \cos \left (t \right ) \]

16597

\[ {}y^{\prime \prime }+4 y = \tan \left (2 t \right ) \]

16598

\[ {}y^{\prime \prime }+y = \csc \left (t \right ) \]

16599

\[ {}y^{\prime \prime }-8 y^{\prime }+16 y = \frac {{\mathrm e}^{4 t}}{t^{3}} \]

16600

\[ {}y^{\prime \prime }-8 y^{\prime }+16 y = \frac {{\mathrm e}^{4 t}}{t^{3}} \]

16601

\[ {}y^{\prime \prime }-2 y^{\prime }+y = {\mathrm e}^{t} \ln \left (t \right ) \]

16602

\[ {}y^{\prime \prime }-2 y^{\prime }+y = {\mathrm e}^{t} \ln \left (t \right ) \]

16639

\[ {}x^{\prime \prime }+x = \left \{\begin {array}{cc} 1 & 0\le t <\pi \\ 0 & \pi \le t \end {array}\right . \]